Lorentz Force Practicum Tool (LoFoPaT): Enhancing Students' Conceptual Understanding in Physics - Mufida, Shobrina Nurul; Samsudin, Achmad; Rusdiana, Dadi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
The Lorentz Force Practicum Tool (LoFoPaT) is a physics learning medium designed to visualize abstract concepts related to the direction of the Lorentz force. This study aims to describe the development of LoFoPaT and its effectiveness in constructing students’ understanding of Lorentz force concepts. The research employed a 4D model (Define, Design, Develop, and Disseminate). During the development stage, the tool was enhanced to generate a larger Lorentz force. Based on assessments by three experts using Mini-Facets Rasch 3.84.0 software, the results indicated that LoFoPaT is valid, though some revisions were suggested. In the dissemination stage, LoFoPaT was implemented with 20 high school students (11 females and 9 males) as research subjects. The Four-tier Instrument on Lorentz Force (FILOF) was used for pre- and post-test questions. The results demonstrated that LoFoPaT is effective in constructing students’ understanding of the Lorentz force at an intermediate level. In conclusion, LoFoPaT can be utilized as a physics learning medium in classrooms to enhance students’ conceptual understanding, particularly in visualizing the direction of the Lorentz force using the right-hand rule.